Identification of charm jets at LHCb; Journal of Instrumentation; Vol. 17, iss. 2 - Aaij R. Roel; Abdelmotteleb A. S.; Beteta C. A. Carlos Abellan; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Vagner A. R. Aleksandr Rudolfovich (2022, 2022)
Title screen